The Evolutionary Game Analysis of Multiple Stakeholders in the Low-Carbon Agricultural Innovation Diffusion - Lixia Liu; Yuchao Zhu; Shubing Guo (Complexity)
Encouraging the adoption and diffusion of low-carbon agricultural technology innovation is an important measure to cope with climate change, reduce environmental pollution, and achieve sustainable agricultural development. Based on evolutionary game theory, this paper establishes a game model among agricultural enterprises, government, and farmers and analyzes the dynamic evolutionary process and evolutionary stable strategies of the major stakeholders. The impact of innovation subsidies, carbon taxes, and adoption subsidies on low-carbon agricultural innovation diffusion is simulated using Matlab software. The results show that the government’s reasonable subsidies and carbon taxes for agricultural enterprises and farmers can increase the enthusiasm of agricultural enterprises and farmers to participate in low-carbon agriculture. This study can be used as a basis for the government to formulate more targeted policies to promote the diffusion of low-carbon agricultural innovation.